Tropical Pacific/Atlantic Ocean interactions at multi‐decadal time scales - Latif, Mojib (Geophysical Research Letters, 2001)
Analysis of sea surface temperature (SST) observations suggests a pan‐oceanic interaction between the tropical Pacific and the Atlantic Ocean at multi‐decadal time scales, such that periods of anomalously high SSTs in the tropical Pacific are followed by a basin‐wide SST dipole in the Atlantic Ocean with a time delay of a few decades. The SST anomaly structure in the Atlantic Ocean is reminscent of variations in the North Atlantic thermohaline circulation. The two ocean basins are linked through an “atmospheric bridge” involving anomalous fresh water fluxes. Based on the observational findings, the Atlantic thermohaline circulation may strengthen during the next decades in response to the strong decades‐long increase in tropical Pacific SST, which will have strong impacts on the climates of North America and Europe through changes in the North Atlantic Oscillation (NAO).